Influence of Plant Growth Regulators on Morphological, Floral and Yield Traits of Cucumber (Cucumis sativus L.) - Mukesh Thappa,; Satesh Kumar,; Romisa Rafiq, (Agriculture and Natural Resources, 2011)
The possibility was examined of altering the plant frame and inducing femaleness at early stages in the development of cucumber for productivity enhancement and early development using various plant growth regulators at the Vegetable Experimental Farm, Division of Vegetable Science and Floriculture, S.K. University of Agricultural Sciences and Technology of Jammu, India during the springsummer season of 2009. Three plant growth regulators were sprayed onto plants at the two-, four- and six-leaf and full-bloom stage using the cucumber variety Cucumber Long Green. Two of the growth regulators, maleic hydrazide and ethephon, were each applied at two different concentrations of 100 and 200 ppm and the third, naphthalene acetic acid, was applied at 50 and 100 ppm, and some combined applications of growth regulators were also tested. The experiment comprised 15 treatments and was laid out in a randomized block design with three replications. The results revealed that the influence of the plant growth regulators was variable on the morphological traits of cucumber but the floral and yield traits were significantly affected by a combined application of 100 ppm maleic hydrazide and 100 ppm ethephon. This treatment induced early development, maximized the sex ratio with regard to yield and was comparatively helpful in reducing plant expansion. This treatment also produced the best economic results for the production of cucumber.